Influence of friction stir processing on microstructure and tensile behavior of AA6061/Al3Zr cast aluminum matrix composites. (February 2019) - Balakrishnan, M.; Dinaharan, I.; Palanivel, R.; Sathiskumar, R.
Graphical abstract: Highlights: Friction stir processing of Al/(0–15 wt.%) Al3 Zr composites. Total rearrangement of particles into a homogenous distribution occurred. Polygonal shape Al3 Zr particles were broken down into fine sized particles. Grain size of cast composites were reduced to extremely fine size. Tensile strength was improved considerable after processing. Abstract: Friction stir processing (FSP) has emerged as an effective secondary processing technique to improve the microstructure and properties of aluminum matrix composites (AMCs). Al/(0–15 wt.%) Al3 Zr AMCs were prepared by adding zirconium powder to molten aluminum and subjected to FSP. The microstructural changes before and after FSP were studied using OM, SEM, EBSD and TEM. Cast composites exhibited coarse grains, segregation, clustering, pores and coarse and sharp-edged polygonal shape particles. The distribution of particles was rearranged into a homogeneous distribution after FSP. Casting defects such as pores were eliminated. The coarse and sharp edged Al3 Zr particles were broken into fine size particles. The grain size reduced remarkably due to severe plastic deformation and the pinning effect of reinforced particles. The density of dislocations increased considerably after FSP. The microstructural changes resulted in an improvement of tensile strength and ductility. The possible strengthening mechanisms were reported.